RISE OF ISLAM IN KASHMIR VALLEY - Shabir Ahmad Lone; Mohammad Ishaq Lone (RADJA PUBLIKA, 2023)
Kashmiri Muslims are ethnic Kashmiris who practice Islam and are native to the Kashmir Valley in Indian-administered Kashmir. Sunni Muslims represent almost all of Kashmiri Muslims. They call themselves